System of Trusteeship for Women of Clerical Rank in Tobolsk Diocese in 1820—1830s - A. V. Spichak (Научный диалог, 2021)
The question of providing financial assistance to women of clerical rank in the Tobolsk diocese in the 1820—1830s is considered. The results of a comparative analysis of the stages and terms of office work on this issue before and after the opening of the Tobolsk guardianship of the poor are presented. Particular attention is paid to the examination of the petition documents that were compiled in the Tobolsk spiritual consistory from the words of women of clerical rank who applied for financial assistance to the Tobolsk archbishop during this period. The novelty of the research is seen in the fact that the issue under consideration is being studied for the first time on the basis of documents of the Tobolsk spiritual consistory. The documents stored in the State Archives in the city of Tobolsk testify to the existence of a certain algorithm for recording a request, two different established procedures for conducting cases on the charity of female clergymen before and after 1823. The criteria, by which the selection of requests was carried out among the many requests for assistance, were identified. Criteria have been established for choosing between two types of salary — a guardianship allowance and a ten-ruble poorhouse salary. The reasons for the complete denial of support are also named.